Mural synodics in private acts of the second half of the 1560s - Alexander Avdeev (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2024)
In the paper created within the framework of the scientific project “Corpus Inscriptionum Rossicarum”, examines two komplex of private acts drawn up in the second half of the 60s of the 16th century by a large Dvinsk landowner Alexej Amosov and boyar Alexej Fyodorovich Bas-manov with the mention of a special type of epigraphic monuments of Moscow Russia — wall synodics or memorial tables. These inscriptions, carved in wood or stone, as well as painted with paint, were placed in the sacred part of the temple, on the wall of the altar opposite the sacrifice. These epigaphic monuments were one of the forms of personal piety, and the right to place them was possessed by the сtitors and donators of the temple or monastery. By their request in the wall synodics records the names of the closest relatives and other people not related to the depositors by ties of kinship. The installation of these epigraphic monuments and their placement in the altar be-came a guarantee of eternal commemoration of the persons inscribed in them during the pros-komidia. The heyday of this type of epigraphic monuments falls on the second half of the 17th — second third of the 18th century, but the earlier period of their existence has not yet served as the subject of special scientific research. Based on the analyzed acts, the paper concludes that at the moment the mention of wall synodics in private acts of the second half of the 60s of the 16th century. They are the earliest evidence of the existence of a stable tradition of creating this type of inscriptions, compiled by order of the ctitors and donators.